1998
DOI: 10.1097/00005392-199805000-00005
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENTIAL EXPRESSION OF URINARY INTER-alpha-TRYPSIN INHIBITOR TRIMERS AND DIMERS IN NORMAL COMPARED TO ACTIVE CALCIUM OXALATE STONE FORMING MEN

Abstract: Immunoreactive profiles of urinary proteins may be able to be developed into a useful diagnostic tool to identify active stone formation, although a separate panel may be required for men and women. It is possible that these differences may provide clues as to why the incidence of stone disease is higher in men than women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…By contrast, Suzuki et al (43) found higher urinary concentrations of BK in male SF compared with healthy male controls and that a greater proportion of SF than normal patients had an aberrant BK 25-kDa species, which is identified to be deglycosylated BK, a form with reduced effectiveness in inhibiting CaOx crystal growth. Marengo et al (14,26) found increased HMM forms (P␣I and ITI), but not BK, in SF (14,26), and these differences were constant over several months (26).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…By contrast, Suzuki et al (43) found higher urinary concentrations of BK in male SF compared with healthy male controls and that a greater proportion of SF than normal patients had an aberrant BK 25-kDa species, which is identified to be deglycosylated BK, a form with reduced effectiveness in inhibiting CaOx crystal growth. Marengo et al (14,26) found increased HMM forms (P␣I and ITI), but not BK, in SF (14,26), and these differences were constant over several months (26).…”
Section: Discussionmentioning
confidence: 92%
“…The ITI family of proteins consists of three heavy chains (H1, H2, H3) of 75-to 85-kDa molecular mass, and one light chain, BK, with a molecular mass of 35-40 kDa (17,39). BK can be linked covalently through its chondroitin-4-sulfate side chain to one or two heavy chains, forming the pre-␣-inhibitor (P␣I; H3ϩBK, 125 kDa) or ITI (H1ϩH2ϩBK, 180 -220 kDa) (8,11,36), also known as ITI-trimer (26). The Ͼ50-kDa bands we detected here most likely correspond to heavy chain components, P␣I or ITI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteopontin (14), prothrombin F1 fragment (15), the inter-α-trypsin inhibitor molecule (16), calgranulin (17), Tamm Horsfall glycoprotein (18), as well as albumin, RNA and DNA fragments, and glycosaminoglycans have all been identified as urine inhibitors of CaOx and CaP crystallization (12). They have in common long stretches of polyanion chains that can bond with surface calcium atoms and prevent crystal growth.…”
Section: Modulators Of the Ulm Crystal Growth And Aggregationmentioning
confidence: 99%